ARGUMENTASI FILSAFAT KENABIAN AL-FARABI DAN IBNU SINA - Faisal Riza (Nizham Journal of Islamic Studies, 2022)
In Islamic intellectual discourse, the concept of the Prophet received various responses from Islamic philosophers. This article examines the arguments of Islamic philosophy regarding prophethood, in this case the arguments of Al-Farabi and Ibn Sina. Using relevant literature related to the two philosophers, this article clarifies the position of Al-Farabi and Ibn Sina's views which affirm their defense of the existence of prophethood. In addition, it is emphasized that prophetic consciousness is a high-level position of mankind. Prophethood is the highest intelligence because it can pick up on heaven's signals and divine messages. Humans who have the highest intellectual as a prophet to be the interpreter of God's will to humans and the universe.